Tibetan Buddhism: artistic, literary, and social legacy - Zreik, Mohamad (IJORESH Indonesian Journal of Religion Spirituality and Humanity, 2024)
Since the 7th century, Tibetan culture and society have been profoundly influenced by Buddhism. This paper aims to explore how Buddhism has shaped Tibetan aesthetics, music, literature, and social structures and to understand its enduring role in Tibetan identity and history. Employing a qualitative research methodology that includes historical analysis, textual interpretation, and ethnographic studies, the paper investigates the development of a unique Tibetan aesthetic tradition, the establishment of monasteries and the monastic system, and the translation and creation of Buddhist texts. Findings reveal that Buddhism has significantly impacted Tibetan art by fostering the creation of intricate religious art forms like thangkas and mandalas, which are central to Tibetan Buddhist practice and reflect a profound spiritual connection between art and religion. The influence of Buddhism on Tibetan literature is evident in the rich body of original, translated, and adapted texts that have shaped Tibetan literary culture and transmitted Buddhist values and philosophies. Furthermore, Buddhism’s centrality in Tibetan society is underscored by the establishment of monasteries and the monastic system, which have been pivotal in preserving Tibetan heritage and culture, providing essential services, and acting as beacons of learning and compassion within the community. The paper recommends further research into the specific ways Buddhist philosophy has influenced Tibetan art and music, the impact of various Buddhist canonical texts on Tibetan literature, and the continuing influence of Buddhism on modern Tibetan society.